2001
DOI: 10.1046/j.1439-037x.2001.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Tillage Systems on Weed Flora in a 3‐Year Rotation with Four Crops

Abstract: Field experiments were conducted to determine the effect of tillage on the dry weight, frequency (PF), density (PD) and species composition of the weed population. Three tillage systems (CT: conventional tillage, MT: minimum tillage and NT: no tillage) were compared in a 3‐year rotation [wheat–vetch (green manure)–cotton–barley]. Decreases in PF, mean PD and number of species were observed under NT because in this system the soil remains undisturbed, and conditions are not suitable for seed germination. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
3
25
2
4
Order By: Relevance
“…(Moonen and Barberi, 2004) were cut in the harvest process. The no-till seeding of cover crops can also reduce the annual weed population density as weed seeds are not incorporated into the soil and germination from the weed seed bank is not induced by tillage (Bilalis et al, 2001). During the cover cropping period, the weed growth will be reduced through cover crop-weed competition for light, water and nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…(Moonen and Barberi, 2004) were cut in the harvest process. The no-till seeding of cover crops can also reduce the annual weed population density as weed seeds are not incorporated into the soil and germination from the weed seed bank is not induced by tillage (Bilalis et al, 2001). During the cover cropping period, the weed growth will be reduced through cover crop-weed competition for light, water and nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…In winter crops, annual species under CT and MT, and perennial species under NT were observed. In cotton, perennial species under CT and MT, and annual species under NT were observed (Bilalis et al, 2001). Greater weed densities in ZT than MT/CoT in a long-term study on a winter wheat-based (T. aestivum L.) cropping systems was noticed.…”
Section: Zero Disturbance Systemsmentioning
confidence: 86%
“…Saccharum spontaneum was observed only in the RT and NT treatments. Bilalis et al (2001) reported more of perennial weeds in the less tilled plots compared to the conventional tillage systems. Weed shifts due to tillage systems cannot be confirmed from this study because observations on weeds from the earlier years of the study are not available.…”
Section: Field Experiments Weed Flora and Densitymentioning
confidence: 96%
“…On the contrary, the RT and NT treatments had less weed diversity because of limited or no tillage intervention, respectively. Low weed diversity in the NT systems have been reported because the soil was undisturbed (Bilalis et al 2001). The conservation tillage systems have crop residue cover that maintains greater soil moisture content and that reduces the weediness as well as a reduction in population diversity (Bilalis et al 2003).…”
Section: Weed Diversitymentioning
confidence: 99%